Predictors for the Bronchiolitis Obliterans Syndrome in Lung Transplant Patient - Sijia YANG (Chinese Journal of Lung Cancer, 2020)
Lung transplantation is the ultimate treatment of end-stage lung disease. After transplantation, the 1-year survival rate is 80%, while the 5-year survival rates remaines at around 50% mainly due to bronchiolitis obliterans syndrome (BOS). BOS is regarded as a fibrosing process in the small airways leading to irreversible airway obstruction. A lot of factors are involved in the development of BOS, such as Ischemia/reperfusion injury, infections, oxidative stress, and acute rejection, etc. Studies have shown that early diagnosis of BOS may improve outcome. It is valuable for the long-term survival of lung transplantation to find out several predictors for the BOS. This article reviews the current state of knowledge on predictors for BOS.